2021
DOI: 10.3389/fmolb.2021.688274
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the Prognostic Value and Gene Expression Mechanism of SHOX2 in Lung Adenocarcinoma

Abstract: Background: Detection of SHOX2 methylation has been used to assist in the early diagnosis of lung cancer in many hospitals as SHOX2 may be important in the tumorigenesis of lung cancer. However, there are few studies on the mRNA expression, methylation, and molecular mechanism of SHOX2 in lung cancer. We aimed to explore the role of SHOX2 in lung adenocarcinoma (LUAD).Methods: First, we examined the differential expression of SHOX2 mRNA and methylation in cancerous and normal tissues using databases. Second, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 39 publications
2
3
0
Order By: Relevance
“…Hereby, mRNA expression was significantly increased with tumor grading and tumor burden. This is in line with previous findings designating SHOX2 as an oncogene [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…Hereby, mRNA expression was significantly increased with tumor grading and tumor burden. This is in line with previous findings designating SHOX2 as an oncogene [ 24 ].…”
Section: Discussionsupporting
confidence: 93%
“…[ 20 ] The relative lower sensitivity of ADC impair diagnostic efficacy of the kit due to a considerate subset of ADCs may present hypomethylation within the SHOX2 gene body. [ 21 ] Notably, although one case each of PECOMA, lymphoma, and metastatic adenocarcinoma showed positive methylation results in this study, the excellent specificity (100%) of methylation detection in distinguishing pulmonary carcinomas from other benign lesions remained consistent with previous studies. [ 18 - 20 , 22 ] However, it is worth mentioning that the DNA concentration of the samples in this study was significantly lower compared to that of other types of pathological specimens reported in the previous research.…”
Section: Discussionsupporting
confidence: 90%
“…Moreover, studies have shown that CNVs play an important role in the progression of cancers, such as lung adenocarcinoma, breast cancer, and ovarian cancer. 29 , 44 , 45 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have reported that CNVs, somatic mutations, and DNA methylation play a crucial role in genetic and epigenetic regulation, especially DNA methylation and CNVs, and correlate closely with oncogenesis and progression. [28][29][30] We searched for CNV levels, somatic mutations and DNA methylation of DLEU2 in KIRC and LIHC using the UCSC Xena website platform. The heat map (Figure 8) results showed that expression of DLEU2 correlated closely with CNVs and DNA methylation, but not with somatic mutations, in both KIRC and LIHC.…”
Section: Cnv Somatic Mutation and Methylation Analyses Of Dleu2mentioning
confidence: 99%